Development of financial sector and implications on monetary transmission mechanism: evidences from Indian economy. (2018) - Laha, Arindam
Monetary policy is often viewed as the tool for stabilising the economy (in particular ensuring price stability). It is generally held that the stimuli of monetary policy are transmitted to the rest of the economy through the development of financial sector. The study attempts to provide empirical evidences on the implications of financial development on the effectiveness of monetary policy in the context of Indian economy over the period 1970-2016. Empirical evidences suggest that Indian economy experiences a significant expansion in the size of financial markets and institutions and it is reflected in the increasing contribution of the financial sector in gross domestic product (GDP) (i.e., depth of the financial development). A disaggregated analysis suggests that development of financial sector impedes in the process of monetary transmission mechanism in the pre-liberalisation period. However, interest rate transmission mechanism remains relatively weak in post-liberalisation period. Thus, development of financial sector does not facilitate the effectiveness of monetary policy in the context of Indian Economy.